My Nation Effectively Utilizes Traditional KPOTI Game Media Through Sustainable Culture - Gandasari, Maharani Fatima; Yantiningsih, Erna (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2025)
Objectives. This study seeks to examine the impact of traditional game media kpoti, guided by the slogan